Effect of gut microbiome-derived metabolites and extracellular vesicles on hepatocyte functions in a gut-liver axis chip - Seong Goo Kang; Yoon Young Choi; Sung Jun Mo; Tae Hyeon Kim; Jang Ho Ha; Dong Ki Hong; Hayera Lee; Soo Dong Park; Jae-Jung Shim; Jung-Lyoul Lee; Bong Geun Chung (Nano Convergence, 2023)
Abstract Metabolism, is a complex process involving the gut and the liver tissue, is difficult to be reproduced in vitro with conventional single cell culture systems. To tackle this challenge, we developed a gut-liver-axis chip consisting of the gut epithelial cell chamber and three-dimensional (3D) uniform-sized liver spheroid chamber. Two cell culture chamber compartments were separated with a porous membrane to prevent microorganisms from passing through the chamber. When the hepG2 spheroids cultured with microbiota-derived metabolites, we observed the changes in the physiological function of hepG2 spheroids, showing that the albumin and urea secretion activity of liver spheroids was significantly enhanced. Additionally, the functional validation of hepG2 spheroids treated with microbiota-derived exosome was evaluated that the treatment of the microbiota-derived exosome significantly enhanced albumin and urea in hepG2 spheroids in a gut-liver axis chip. Therefore, this gut-liver axis chip could be a potentially powerful co-culture platform to study the interaction of microbiota and host cells. Graphical Abstract